Analisis Kinerja Keuangan Dengan Rasio Keuangan PT. Indofood Sukses Makmur Tbk - Intan Septiani; Herudini Subariyanti (Journal of Management and Social Sciences, 2023)
Analysis of financial performance with financial ratios of PT. Indofood Sukses Makmur TBK, can be done through financial ratio analysis. The aim of this research is to determine the liquidity ratio, activity ratio and profitability ratio at PT. Indofood Success Makmur TBK. The research method used is a quantitative research method. Quantitative research is carried out by collecting data in the form of numbers, or data in the form of words or sentences which are converted into data in the form of numbers. In the context of PT. Indofood Sukses Makmur Tbk, this financial ratio analysis will provide a view of the company's performance in generating profits, managing liquidity, managing debt and utilizing its assets. However, it should be remembered that financial ratio analysis should not only depend on one indicator, but must be seen as a whole and in the context of the relevant industry. From the results of this research it was found that the activity ratio was good, the profitability ratio was quite good, the liquidity ratio was quite good.